Nutritional status and malaria infection in primary school-aged children - Washli Zakiah; Tiangsa Sembiring; Lily Irsa (Paediatrica Indonesiana, 2015)
Background The most common nutritional problem affecting the pediatric population in developing countries is protein energy malnutrition (PEM). The nutritional problem may be caused by a variety of factors, most of which are related inadequate food intake and infection. One of the highest causes of morbidity and mortality in endemic areas is malaria. Malaria infection and nutritional status have been suggested to be interrelated.Objective To assess for a relationship between nutritional status and malaria infection in children.Methods This cross-sectional study was conducted in October and November 2010 in primary school children at Panyabungan City, North Sumatera Province. Peripheral thick and thin blood smear examinations were done to confirm the diagnosis of malaria. Participants were divided in two groups (malaria-infected and uninfected) by consecutive sampling. Nutritional status was determined by body weight and height measurements based on the 2000 Centers for Disease Control and Prevention (CDC) chart. The mild and moderate malnutrition classification was further sub-divided into stunted and wasted, based on the 2007 NCHS/WHO chart. Chi-square test was used to analyze the relationship between nutritional status and malaria infection.Results There were 126 children in each group. Significant differences in mild-moderate malnutrition were found between the malaria-infected and uninfected groups (23.8% vs. 46.8%, respectively; P= 0.011). There were also significant differences between the malaria-infected and uninfected groups with regards to chronic malnutrition type: stunted (20.0% vs. 37.3%, respectively; P=0.042) and stunted-wasted (6.7% vs. 28.8%, respectively; P= 0.008) in both groups of the children with mild-moderate malnutrition.Conclusion There are significantly more children with mild-moderate malnutrition in the uninfected group than in the malaria-infected group, furthermore, of those with mild-moderate malnutrition, there are significantly more stunted and stunted-wasted children who were uninfected than malaria-infected.